Reviews on family, comunication and social change reflections on the work of Virginia Gutiérrez de Pineda and Gino Germani: Reflexiones en torno a la obra de Virginia Gutierrez de Pineda y Gino Germani - Barrios, Marta Milena (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
In the following essay, Virginia Gutierrez de Pineda and Gino Germani´s points of view are discussed from the identification of some common categories: family and social change. This, as part of an initial exercise, which has the goal to rescure value of investigations about the repercussions affecting the coreo f families, every time a Latin American country goes trough is rather continuous struvtural transfomations.